PRESERVATION AND MUSEUMIFICATION OF THE ARCHITECTURAL ENSEMBLE “MEZHIBIZH FORTRESS” WITHIN THE ACTIVITIES OF THE STATE HISTORICAL AND ARCHITECTURAL RESERVE “MEZHIBIZH” (Південний архів (історичні науки), 2023)
The purpose of the work is to determine the main stages of the organization of monument preservation activities in the Mezhibyzh Fortress, and the role of the State Historical and Architectural Reserve “Mezhibyzh” in the field of protection, study, preservation, restoration and museification of the fortification and palace ensemble in the village Medzhibyzh. Research methods. In accordance with the established goal, the research uses a dialectical approach aimed at tracing the main stages of the development of the monument protection case on the basis of the fortress in Medzhibozh. The territorial research method is used. The main focus is on the territory of the fortification and palace complex in the village of Medzhibyzh, Khmelnytskyi region. The structural-thematic method is used in the process of analyzing historiography and cause-and-effect relationships between historical processes and their influence on modern approaches in the work of the historical and architectural reserve “Mezhybyzh”. The results. The main stages of the formation and development of the architectural defense complex in Medzhibozh have been elaborated. The main stages of the organization of the monument protection case regarding the Medzhibizh fortress are considered separately. Conclusions. It was established that the initial stage for the organization of monument protection work on the basis of the fortress in Medzhibozh was the 1950s – 1960s.At the initial stage, separate restoration and conservation measures were carried out, aimed at adapting the fortress to Soviet needs. Research institutes played a key role in the process of preserving and restoring the fortress. During the 1970s and 1980s, a number of scientific research and repair and restoration works were carried out on the basis of the defense structures of Medzhibozh. However, the complex preservation of the ensemble of monuments in Medzhibozh was carried out at an unsatisfactory level for a long time, which led to the building's disrepair. Special attention is paid to the activity of the State Historical and Architectural Reserve “Mezhybyzh” in the field of organization of protection and museification of the architectural defense complex of monuments that is part of it. The main directions of work and achievements of the State Historical and Architectural Reserve “Medzhibyzh” in the field of monument protection have been established, and gaps in the work of the institution have also been identified. In this way, the conservation activities of the “Mezhybyzh” nature reserve, aimed at the preservation and museification of the Fortification complex, have been considered.
Keywords: object of fortification art, monument, protection, restoration, scientific research activity, reserve Khmelnytskyi region, museification